Capoeira Pedagogy and Bodily Knowledge in Mexico City: Me diga quem foi seu Mestre? - Islas, David Sebastian Contreras; Luna, Erick Serna; Gonzalez Varela, Sergio Armando (Martial Arts in Latin Societies, 2025)
Based on (auto)ethnographic work and the embodied experience of the authors, this chapter explores the pedagogical processes of teaching and learning in Capoeira groups in Mexico City. To that end, it reflects on the bodily knowledge that underlies these pedagogical processes: on the one hand, how people transmit these practices in their various groups; on the other hand, how the authors, as practitioners, have incorporated and experienced this embodied knowledge. To this end, the authors compare their teaching and learning experiences with three different styles of this art: Angola, the contemporary style of Minas Gerais, and the contemporary style of Mexico City. For reasons of space, the study is limited to the pedagogical processes that take place in Capoeira classes. The analysis shows how the teaching and learning processes in the Capoeira classrooms of Mexico reproduce and recreate the rituals of the Capoeira tradition in their pedagogical structures, in which a dialectical process is at play between learning and the production of new bodily knowledge.
Created from Fastlane, Scopus look-up